Estudio de patología para la Casona, Monumento Nacional (2015)
The Escuela Colombiana de lngenieria, is located on the grounds of an ancient hacienda in the savannah of Bogota. You will find an architectural national monument called the Casona, that mainly by acts of vandalism was partly destroyed and the part that survived is currently very impaired. By its character as a national monument, the Escuela has the obligation to restore it. The Casona has was built in two stages; the first one oriented from south to north, was built with adobe and covered with clay tile supported by wood trusses. The second one oriented from east to west with brick walls and cover similar to the first stage. One part is only one story high and there is another with a three stories tower. The house was built more than 100 years ago, when Earthquake Resistant Standards didn‘t exist in Colombia. In the history of La Casona no structural reform has been made so far. For this reason, the purpose of this this work was to develop a study of la Casona's Pathology and to sketch an idea for its strengthening ln the study of pathology were inspected the structural system and its foundations; in addition a brick taken from a wall, was tested under axial compression in order to obtain at Ieastone idea of its strength. Based on the study of pathology, the structural investigation of the house was performed diagnosis is given on its causes and state of damage and recommendations are given for its maintenance in order to avoid further deterioration.